(untitled) (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
Tooth extractions for orthodontic purposes has been a topic discussed for over a hundred years and, currently, the criteria that determine the choice of this form of treatment go beyond the analysis of models and the position that the teeth are in the bone base. The aim of this study was to analyze the indications for extractions, which teeth are extracted most frequently, and post-treatment stability. The study was developed from an electronic search in PubMed/Medline and Google Scholar databases. Articles published over a 10-year period were selected that addressed extractions in the treatment plan. Duplicate articles in both databases and those that did not address the topic of Extractions were excluded. 468 articles were found in PubMed and 152 in Google Scholar, 472 were excluded, 153 articles were examined, reaching the selection of 37 articles and, of these, only 12 were used for the development of this work. The extractions are indicated in cases of dental and skeletal discrepancies, protrusion or biprotrusion and ortho-surgical treatments. The main teeth to be extracted are the maxillary premolars due to their location in the arch and post-treatment stability was similar to cases where extractions are not chosen in the treatment plan.